La llegenda del cor menjat al Decameró de Boccacció: estratègies de traducció al català. - TARRÉS, MARIBEL CAMPMANY (Scripta, 2013)
The extent to which translators intervene in a text determines its approach to the reader. By comparing the four Catalan translations of The Legend of the Eaten Heart, the ninth tale of the fourth day of The Decameron by Giovanni Boccaccio, you can see that each translator uses different strategies to tackle the same translation problem. Besides each translator's cultural background and subjectivity, one must take into account several factors (time, history, reference, language, society, etc.), which might also affect the outcome.